Postnationalist Ireland : politics, culture, philosophy - Kearney, Richard (Routledge, 1997)
"The encroachment of globalization and demands for greater regional autonomy have had a profound effect on the way we picture Ireland. This challenging new look at the key question of sovereignty asks us how we should think about the identity of a 'postnationalist' Ireland. Richard Kearney goes to the heart of the conflict over demand for communal identity, traditionally expressed by nationalism, and the demand for a universal model of citizenship, traditionally expressed by republicanism. In so doing, he asks us to question whether the sacrosanct concept of absolute national sovereignty is becoming a luxury ill-afforded in the emerging new Europe." "Kearney then takes us beyond the political with chapters on the influence of such philosophers as George Berkeley, John Toland and John Tyndall and looks at some of the myths in Irish poetry and nationhood." "Postnationalist Ireland provides a recasting of contemporary Irish politics, culture, literature and philosophy and will appeal to students of these subjects and Irish studies in general."--Jacket